1983
DOI: 10.1190/1.1441476
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aeromagnetic measurements from the Cascade Range in central Oregon

Abstract: Shallow Curie‐point isotherm depths, indicated by the analysis of magnetic anomalies, young silicic volcanism, hot springs, and high heat flow mark the Cascade Range of central Oregon as a potentially important geothermal resource area. Aeromagnetic measurements in the central Cascades between 43°00′ and 44°15′N latitude and 121°00′ and 122°30′W longitude exhibit predominant northwest‐southeast lineations and less prominent north‐northeast by south‐southeast lineations. Longer wavelength components of the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
4

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(104 citation statements)
references
References 17 publications
1
99
0
4
Order By: Relevance
“…Thus the Curie temperature isotherm corresponds to the basal surface of magnetic crust and can be calculated from the lowest wavenumbers of magnetic anomalies, after removing the approximate regional field from the aeromagnetic data (e.g. Bhattacharyya and Morley 1965;Spector and Grant 1970;Mishra and Naidu 1974;Byerly and Stolt 1977;Connard et al 1983;Hamdy et al 1984;Blakely 1988;Tanaka et al 1999;Salem et al 2000;Ross et al 2006). …”
Section: Regional Magnetic Feature and Geologymentioning
confidence: 99%
“…Thus the Curie temperature isotherm corresponds to the basal surface of magnetic crust and can be calculated from the lowest wavenumbers of magnetic anomalies, after removing the approximate regional field from the aeromagnetic data (e.g. Bhattacharyya and Morley 1965;Spector and Grant 1970;Mishra and Naidu 1974;Byerly and Stolt 1977;Connard et al 1983;Hamdy et al 1984;Blakely 1988;Tanaka et al 1999;Salem et al 2000;Ross et al 2006). …”
Section: Regional Magnetic Feature and Geologymentioning
confidence: 99%
“…Also, as noise in the spectra can affect the quality of the CPD computation, we provide a map of misfit between the observed and the theoretical spectra for each CPD computation window. The theoretical radial power spectrum of magnetic anomalies derived from the shape of the Fourier radial power spectrum, as presented in this study, is derived from the following equation [e.g., Connard et al, 1983;Okubo et al, 1985;Blakely, 1988;Tanaka et al, 1999;Ross et al, 2006]…”
Section: Methodsmentioning
confidence: 99%
“…Okubo et al (1985Okubo et al ( , 2003 suggested the optimal dimensions of the investigated square window to be about ten times the actual target depth (Hisarli et al 2011). Connard et al (1983) divided a magnetic data of the Cascade Range, central Oregon, into overlapping blocks (77 × 77 km) and calculated the radially average power spectrum for each block. Tanaka et al (1999) divided the East and Southeast Asia into sub-region data (approximately 200 × 200 km) and estimated the power density spectra for each region.…”
Section: Data Processing and Analysismentioning
confidence: 99%